P620 Stapled end-to-side vs. side-to-side anastomosis after ileocecectomy for Crohn's disease: a propensity score-matched analysis. (25th January 2019) - Brandstetter, S; Gouvea Monteiro de Camargo, M; Aiello, A; Stocchi, L; Church, J M; Hull, T; Lavery, I; Steele, S R; Holubar, S; Valente, M
Abstract: Background: Ileo-colic resection (ICR) is the most common surgical procedure for Crohn's disease (CD). Anastomotic construction is most commonly achieved with stapled side-to-side (SSTS) or hand-sewn end-to-end anastomosis (ETE). Another option that combines advantages of both SSTS and ETE is the stapled end-to-side anastomosis (SETS). However, results after SETS have not previously been reported. We aimed to compare short-term septic complications and long-term recurrence-free survival (RFS) of CD between patients who underwent SETS vs. SSTS. Methods: This study was a retrospective analysis of a prospectively maintained database. All patients who underwent resection and anastomosis for terminal ileal CD from 01/2012–12/2016 were included. Patients with a stoma, or other type of anastomosis were excluded. Surgeries were done for 27 surgeons. Groups were compared with univariate analysis. RFS (Rutgeerts ≥ i2 or active disease on CT/MRI) was assessed using Kaplan–Meier curves and a log-rank test. Cox-proportional hazard and linear regression models with propensity score inverse probability of treatment weighting were used to further evaluate postoperative outcomes and recurrence of CD. Numbers represent median or proportion as noted. Results: A total of 383 patients were analysed: 181 with SETS and 202 with SSTS. There were no differences regarding demographics and disease characteristics, except SETS patients had less weight loss (8% vs. 15%, p = 0.04) and fewer phlegmons (5% vs. 10%, p = 0.05). SETS operations were shorter (120 vs. 133 min, p = 0.02), and fewer were performed laparoscopically (46% vs. 65%, p = 0.001). Patients who underwent SETS compared with STSS had more experienced surgeons (23 vs. 11 years, p < 0.001). There was no difference in any short-term outcome on univariate analysis. RFS Kaplan–Meier analysis showed no difference in recurrence rates. After inverse probability of treatment weighting using the propensity score and number of postoperative medications, there was no significant difference in any of the outcomes between the two groups. Conclusions: At our centre, SETS and SSTS anastomoses in patients undergoing ICR for CD were comparable with respect to short-term complications and long-term recurrence rates. Therefore, SETS remains a viable method for reconstruction, especially in the case of bowel lumen size mismatch.